TARBIYAH SHALAT QABLIYAH DAN BA’DIYAH DARI RASULULLAH - masrur, imam (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2021)
Hadith is an urgent thing in Islamic knowledge. It is the second source in Islam after Quran which explains the global massage of Quran. It explains the daily activities like Qabliyah and Ba’diyah clearly. But in the fact,  Fiqh  hegemony dominates the Muslims daily activities than understanding to hadits. It happens especially to the Muslims in Indonesia. Fiqh becomes the standard and the major in facing a life’ problem. So, the researcher will present how the real hadist is in explaining af’aliyah of Rasulullah relates to shalat Qabliyah and Ba’diyah based on ulama hadist’ view.  This research uses a thematic hadith method. It is collecting the hadits which have a same theme which discuss about shalat Qabliyah and Ba’diyah of Rasulullah. Firstly, he will explain the validation of hadist’ quality, then understanding to hadits. It can be used as manual interpretation. The local of this research is kutub al-tis’ah, and for the understanding is by sharh   Some conclusions from this research are Rasulullah did shalat Qabliyah and ba’diyah. Qabliyah subuh is two rakaat, then He slept till the muadzin iqamat. Qabliyah duhur is two or 4 rakaat. Ba’diyah dhuhur is two rakaat. Qabliyah Ashar is 4 rakaat by 2 salam. For Qabliyah maghrib, rasulullah commands to do it for the people who wish it. But, do not consider that it is a fervent. Ba’diyah maghrib is two, and ba’dyah isya’ is two also.  Key Words: Hadith, Qabliyah-Ba’diyah, Interpretation.